2013
DOI: 10.1007/s00423-013-1137-7
|View full text |Cite
|
Sign up to set email alerts
|

ENERgized vessel sealing systems versus CONventional hemostasis techniques in thyroid surgery—the ENERCON systematic review and network meta-analysis

Abstract: This meta-analysis shows superiority of ultrasonic devices in terms of operation time compared with conventional hemostasis techniques in thyroid surgery, with no detriment to safety outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 50 publications
6
60
0
2
Order By: Relevance
“…Many studies in the literature have compared these two techniques, and no superiority has been detected in terms of efficiency. However, some studies indicated superiority of vessel sealing systems in terms of operation time as compared to conventional hemostasis techniques in thyroid surgery, with no detriment to safety outcomes (18). Sutures with a low risk for reaction and especially absorbable sutures should be preferred especially for upper pole ligation, as in our practice.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the literature have compared these two techniques, and no superiority has been detected in terms of efficiency. However, some studies indicated superiority of vessel sealing systems in terms of operation time as compared to conventional hemostasis techniques in thyroid surgery, with no detriment to safety outcomes (18). Sutures with a low risk for reaction and especially absorbable sutures should be preferred especially for upper pole ligation, as in our practice.…”
Section: Discussionmentioning
confidence: 99%
“…The Harmonic FOCUS ® (HF; Ethicon Endo-Surgery, Inc.) comprises a range of ultrasonic surgical devices that enable simultaneous dissection and coagulation of tissue (2). Ultrasonic waves are created by electromagnetic energy from a generator, which undergoes piezoelectric transduction within the hand piece.…”
Section: Introductionmentioning
confidence: 99%
“…Energy based devices (EBD) have been developed, implemented and increasingly applied in thyroid surgery because they can provide a combined dissection and haemostatic effect (6,7). In particular, advantages of EBD have been described in terms of efficacious haemostasis, reduction of procedure-associated time, reduced incision length, less operative blood loss and transfusion need, decreased postoperative drain, pain and hospital stay (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%